2015
DOI: 10.1590/1679-78251290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CFRP retrofit on impact response of shear-deficient scaled reinforced concrete beams

Abstract: An experimental procedure is carried out to investigate response features of semi-deep reinforced concrete (RC) beams with dominant static shear failure subjected to low-velocity impact dynamic load both in intact and retrofitted cases. Built specimens have scaled geometry and material properties preserving physical similarity with full-scale members and are strengthened using externally bonded carbon fiber reinforced polymer (CFRP) sheets. Conducted tests gather reliable and robust data revealing notable stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Some researchers [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] found that strengthening with carbon-fiber-reinforced polymer (CFRP) composite wraps could improve the shear impact resistance of RC beams, prevent the development and expansion of shear cracks, and eventually restrict the shear damage. Suter et al [ 15 ] found earlier that wrapping RC columns transversely with aromatic fiber (Kevlar) composites could significantly enhance the shear impact resistance of columns.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] found that strengthening with carbon-fiber-reinforced polymer (CFRP) composite wraps could improve the shear impact resistance of RC beams, prevent the development and expansion of shear cracks, and eventually restrict the shear damage. Suter et al [ 15 ] found earlier that wrapping RC columns transversely with aromatic fiber (Kevlar) composites could significantly enhance the shear impact resistance of columns.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the studies indicate that it is very promising to utilize FRP sheets in strengthening concrete components. However, very limited literature investigates the dynamic response of FRP-shear-strengthened RC specimens under impact loads (Soleimani et al) [6][7][8][9]. Shafei and Kabir carried out a drop-hammer test on shear-strengthened RC beams with two kinds of FRP sheets, that is, unidirectional fiber and cross-fiber FRP [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, very limited literature investigates the dynamic response of FRP-shear-strengthened RC specimens under impact loads (Soleimani et al) [6][7][8][9]. Shafei and Kabir carried out a drop-hammer test on shear-strengthened RC beams with two kinds of FRP sheets, that is, unidirectional fiber and cross-fiber FRP [7]. e results show that both FRP sheets can reduce the deflection of the members, restrain the development of shear cracks, reduce the degree of damage, and increase the energy absorption capacity of the members.…”
Section: Introductionmentioning
confidence: 99%